Long-life electroluminescent device and preparation method thereof

Through the CL-passivation processing of quantum dot nuclear and electronic transmission materials, the problem of lack of light and service life of the existing QLED device has been solved, and higher thermal stability and charge injection/transmission efficiency have been achieved, which significantly improves the significant improvement, which has improved significantly, which has significantly improved Life of the device.

CN119364995APending Publication Date: 2025-01-24SUZHOU XINGSHUO NANOTECH CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411425941.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-12
Publication Date
2025-01-24

AI Technical Summary

Technical Problem

The luminous efficiency and service life of existing QLED electroluminescent devices have not yet met the requirements of industrialization.

Method used

By etching and passivating inorganic acid/acid and chloride on the surface of the quantum dot core, and introducing Cl-ligands into the electron transport material, Cl-passivated quantum dots and electron transport materials are formed to improve the performance of the device. Thermal stability and charge injection/transfer efficiency.

Benefits of technology

Significantly improves the life of QLED devices, T50@1000nits can reach more than 60h, improving the thermal stability and charge injection/transmission efficiency of the device.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119364995A_ABST
    Figure CN119364995A_ABST
Patent Text Reader

Abstract

The invention provides a long-life electroluminescent device and a preparation method thereof, and the device comprises an anode substrate, a hole injection / transmission layer, a quantum dot light-emitting layer, an electron transmission layer and a cathode which are sequentially stacked. The quantum dot light-emitting layer comprises quantum dots, each quantum dot comprises a core body and a shell layer wrapping the core body, and the surface of each core body is etched and passivated by inorganic acid / acid and chloride at the same time; the electron transport layer comprises an electron transport material, and the electron transport material is passivated by chloride.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application belongs to the technical field of display devices, and specifically relates to a long-life electroluminescent device and a preparation method thereof. Background Art

[0002] Quantum dots, also known as semiconductor nanocrystals, are a new type of semiconductor nanomaterial with a size of 1-10nm. Due to the quantum size effect and dielectric confinement effect, they have unique photoluminescence (PL) and electroluminescence (EL) properties. Compared with traditional organic fluorescent dyes, quantum dots have high quantum yield, high photochemical stability, not easy to photolyze, as well as wide excitation, narrow emission, high color purity, and the luminescent color can be adjusted by controlling the size of quantum dots. Excellent optical properties have broad application prospects in the field of display technology. Among them, quantum dots are applied to electroluminescent devices, QLED (quantum dot light emitting diode) devices, which have the advantages of adjustable emission wavelength in the visible light range, narrow half-width, high brightness, and solution method preparation. However, despite the continuous optimization of QLED devices (for example, Chinese patent CN110729406B discloses a mixed hole injection layer QLED device and a preparation method thereof, and improves the life of the QLED device by improving the hole injection layer material. Chinese patent CN116156915A discloses a QLED device and a preparation method thereof, a display panel, and improves the life of the QLED device by an improved hole recombination layer.), the performance of existing QLEDs has been greatly improved, but its luminous efficiency (especially device life) is still far from meeting the requirements of industrialization.

[0003] In view of this, the present application provides a long-life electroluminescent device and a preparation method thereof to improve the electroluminescent performance, especially the service life. Summary of the invention

[0004] The purpose of the present application is to provide a long-life electroluminescent device and a preparation method thereof, so as to improve the electroluminescent performance, especially the service life.

[0005] In a first aspect of the present application, a long-life electroluminescent device is provided, wherein the electroluminescent device comprises an anode substrate, a hole injection / transport layer, a quantum dot light-emitting layer, an electron transport layer and a cathode which are stacked in sequence;

[0006] The quantum dot light-emitting layer comprises quantum dots, the quantum dots comprise a core body and a shell layer covering the core body, and the surface of the core body is etched and passivated simultaneously by an inorganic acid / acid and chloride;

[0007] The electron transport layer includes an electron transport material, wherein the electron transport material is chloride (Cl - ) passivation.

[0008] In some embodiments, the anode substrate includes: a substrate and an anode.

[0009] In some embodiments, the hole injection material of the hole injection layer includes transition metal oxide nanowires, or conductive polymer PEDOT:PSS.

[0010] In some embodiments, a hole transport layer is further disposed between the hole injection layer and the quantum dot light-emitting layer.

[0011] In some embodiments, the core of the quantum dot is a Group IIB-VIA element.

[0012] Further, the core of the quantum dots includes: ZnSe, ZnTe, ZnSeTe, ZnSeS, ZnSTe, CdSe, CdTe, CdSeTe, CdSeS, CdSTe, CdZnS, CdZnSe, CdZnTe, HgS, HgSe, HgTe, HgSeS, HgSeTe, HgSTe, CdHgS, CdHgSe, CdHgTe, HgZnS, HgZnSe, HgZnTe, HgZnTeS, CdZnSeS, CdZnSeTe, CdZnSTe, CdHgSeS, CdHgSeTe, CdHgSTe, HgZnSeS, HgZnSeTe, HgZnSTe or a combination thereof.

[0013] In some embodiments, the inorganic acid / acid comprises at least one of hydrofluoric acid, hydrogen chloride, sulfuric acid, formic acid, acetic acid, sodium fluoride, aluminum fluoride, calcium fluoride, lead tetrafluoride, phenylcarbonyl fluoride, tetrabutylammonium fluoride, fluoroacetamide, or sodium fluoroacetate.

[0014] In some embodiments, the chloride consists of a metal element and a chlorine element.

[0015] Furthermore, the chloride includes at least one of zinc chloride, potassium chloride, sodium chloride, copper chloride, magnesium chloride, calcium chloride, ferric chloride, ferrous chloride, or aluminum chloride.

[0016] In some embodiments, the electron transport material includes: metal oxide, core-shell structure metal oxide, element-doped metal oxide, element-doped core-shell structure metal oxide.

[0017] Furthermore, the metal oxide includes: at least one of zinc oxide, magnesium oxide, zinc magnesium oxide, aluminum oxide, and zinc aluminum oxide; the core-shell structured metal oxide includes: at least one of zinc magnesium oxide / magnesium oxide, zinc magnesium oxide / zinc oxide, zinc oxide / magnesium oxide, zinc aluminum oxide / magnesium oxide, zinc aluminum oxide / zinc oxide, zinc aluminum oxide / aluminum oxide, and zinc oxide / aluminum oxide; the metal oxide doped with elements or the core-shell structured metal oxide doped with elements is a metal oxide or a core-shell structured metal oxide doped with other elements, and the doping elements include: at least one of aluminum, lithium, tin, manganese, yttrium, lanthanum, copper, nickel, zirconium, cerium, and gadolinium.

[0018] In some embodiments, the material of the cathode includes at least one of aluminum, magnesium, calcium, silver and alloys thereof.

[0019] The second aspect of the present application provides a method for preparing a long-life electroluminescent device, the method comprising: sequentially arranging a hole injection layer, a hole transport layer, a quantum dot light-emitting layer, and an electron transport layer on an anode substrate, and forming a cathode layer or a packaged cathode plate on the electron transport layer to obtain an electroluminescent device; wherein,

[0020] The quantum dot light-emitting layer includes quantum dots, after synthesizing the quantum dot core body, adding inorganic acid / acid and chloride to etch and passivate it, and then synthesizing the shell layer covering the core body;

[0021] The electron transport layer includes an electron transport material. When synthesizing the electron transport material, chloride is added to passivate it to form Cl - Passivated electron transport materials.

[0022] In some embodiments, the inorganic acid is added in a molar ratio of 1:(200-5000) to the acid and chloride.

[0023] Furthermore, the inorganic acid is added in a molar ratio of 1:(500-2000) to the chloride.

[0024] Furthermore, the diameter of the core is 4.0-4.5 nm, and the thickness of the shell is 2.4-3.5 nm.

[0025] In some embodiments, when the electron transport material is a metal oxide or a metal oxide doped with elements, the chloride is added after the metal oxide or the metal oxide doped with elements is synthesized; when the electron transport material is a core-shell structure metal oxide or a core-shell structure metal oxide doped with elements, the core-shell structure metal oxide or the core-shell structure metal oxide doped with elements comprises an oxide core and an oxide shell layer covering the oxide core, and after the oxide core is synthesized, the chloride is added, and then the oxide shell layer is synthesized.

[0026] Compared with the prior art, the long-life electroluminescent device and the preparation method thereof of the present application have at least the following advantages:

[0027] (1) After the quantum dot core is synthesized, chloride is added to introduce Cl - Replacing some OA ligands can improve the thermal stability of the device and the injection / transfer efficiency of charges. Among all the ligands that can bind to Zn dangling bonds, Cl- binds more strongly to cation dangling bonds such as Zn, making the surface energy stable. DFT calculations show that the mid-band gap trap state close to the valence band maximum in the Zn-OA passivated surface is replaced by the addition of Cl - Elimination, which means that Cl - Replacing OA can improve the quantum yield of quantum dots.

[0028] (2) After the synthesis of the quantum dot core, adding inorganic acid / acid and chloride can greatly eliminate the stacking fault, thereby improving the photoinduced and electroinduced properties of the product. At the same time, there is a synergistic effect between inorganic acid / acid and chloride. The inorganic acid / acid can separate the ligand by protonation, while the chloride can replace the bulky fatty acid ligand to coordinate with the dangling bond of the passivated surface.

[0029] (3) Introducing Cl into electron transport materials - Ligands can replace part of the ligands on the surface of the electron transport material, reduce the steric hindrance effect of the ligands on the surface, and improve the spin coating film forming property. At the same time, the smaller steric hindrance effect of the ligands can increase the coverage of the ligands on the surface of the electron transport material and improve its stability.

[0030] (4) In QLED devices, the surface of the quantum dot core is covered with Cl - By replacing some OA ligands and passivating them, the electron transport material is also - Ligand coordination and passivation, while using Cl - There is a synergistic effect between the passivated quantum dots and the electron transport material, which significantly promotes the injection, transmission and recombination of charges between the quantum dot light-emitting layer and the electron transport layer, promotes the occurrence of radiative recombination, and significantly improves the life of the QLED device composed of the two. - QLED devices made of passivated quantum dots and electron transport materials can achieve T50@1000nits of more than 60h. BRIEF DESCRIPTION OF THE DRAWINGS

[0031] Combined with the following Figure 1When read together, the above and other features of the present application will be more fully described. It is understood that these drawings only depict several implementations of the present application and should not be considered as limiting the scope of the present application. By using the drawings, the present application will be more clearly and detailed.

[0032] Figure 1 This is a photograph of the QLED device of Example 1 in the illuminated state.

[0033] Figure 2 Graph showing the relationship between current density (J) and brightness (L) of the QLED device of Example 1.

[0034] Figure 3 Graph showing the relationship between current efficiency (CE) and brightness (L) of the QLED device of Example 1.

[0035] Figure 4 Graph showing the relationship between the external quantum efficiency (EQE) and brightness (L) of the QLED device of Example 1. DETAILED DESCRIPTION

[0036] The following examples are described to assist the understanding of the present application, and the examples are not and should not be interpreted in any way as limiting the scope of protection of the present application.

[0037] If not otherwise defined, all terms (including technical and scientific terms) in this specification may be defined as commonly understood by those skilled in the art to which the present disclosure belongs. It will be further understood that terms, such as those defined in commonly used dictionaries, should be interpreted as having a meaning consistent with their meaning in the context of the present disclosure and the relevant art, and will be interpreted in a non-idealized or overly formal sense unless clearly defined as such in this article.

[0038] As used herein, the term "at least one", when before or after a list of elements, modifies the entire list of elements without modifying the individual elements of the list, and will not be interpreted as limiting "one". "Or" means "and / or". The terms "include" and "comprise", when used in this specification, indicate the presence of the stated features, regions, wholes, steps, operations, elements, and / or components, but do not exclude the presence or addition of one or more other features, regions, wholes, steps, operations, elements, components, and / or their collections. Therefore, the above wording will be understood to mean including the stated elements, but not excluding any other elements. The term "and / or" includes any and all combinations of one or more of the associated listed items. The term "multiple" refers to two or more. The term "connection" refers to direct or indirect connection. It will be understood that when an element such as a layer, film, region, or substrate is referred to as "on" another element, it may be directly on the other element or there may also be an intermediate element. On the contrary, when an element is referred to as "directly on" another element, there is no intermediate element. In order to clearly illustrate the embodiments in the figures, some parts that are not actually related to the description may be omitted. The terms "first", "second", "third", etc. may be used herein to describe and distinguish various elements, components, regions, layers and / or parts, but these elements, components, regions, layers and / or parts should not be limited by these terms.

[0039] In a first aspect of the present application, a long-life electroluminescent device is provided, wherein the electroluminescent device comprises an anode substrate, a hole injection / transport layer, a quantum dot light-emitting layer, an electron transport layer and a cathode which are stacked in sequence;

[0040] The quantum dot light-emitting layer comprises quantum dots, the quantum dots comprise a core body and a shell layer covering the core body, and the surface of the core body is etched and passivated simultaneously by an inorganic acid / acid and chloride;

[0041] The electron transport layer includes an electron transport material, wherein the electron transport material is chloride (Cl - ) passivation.

[0042] In some embodiments, the anode substrate comprises: a substrate and an anode. The materials of the substrate and the anode are materials known in the art, the substrate comprises a rigid substrate or a flexible substrate, the material of the substrate comprises: at least one of glass, polyacetamide (PI), polyvinyl alcohol (PVA), or polyethylene naphthalate (PEN); the anode comprises ITO, FTO, or AZO.

[0043] In some embodiments, the hole injection material of the hole injection layer includes transition metal oxide nanowires or conductive polymer PEDOT:PSS. The solvent for dissolving the hole injection material may be a known solvent in the art, such as water, methanol, ethanol or acetonitrile, etc., which is not specifically limited here.

[0044] In some embodiments, a hole transport layer is further provided between the hole injection layer and the quantum dot light-emitting layer. The hole transport material of the hole transport layer includes at least one of TFB (poly (9,9-dioctylfluorene-CO-N-(4-butylphenyl) diphenylamine)), P3HT (3-hexyl substituted polythiophene), PVK (poly (9-vinyl carbazole)), poly-TPD (poly [bis (4-phenyl) (4-butylphenyl) amine]), TCTA (4,4',4'-tri (carbazole-9-yl) triphenylamine), or CBP (4,4'-di (9-carbazole) biphenyl). The organic solvent for dissolving the hole transport material may be a known solvent in the art, for example: dichlorobenzene, chlorobenzene, toluene, xylene, etc., which are not specifically limited here.

[0045] In some embodiments, the core of the quantum dot is a Group IIB-VIA element.

[0046] Further, the core of the quantum dot includes: ZnSe, ZnTe, ZnSeTe, ZnSeS, ZnSTe, CdSe, CdTe, CdSeTe, CdSeS, CdSTe, CdZnS, CdZnSe, CdZnTe, HgS, HgSe, HgTe, HgSeS, HgSeTe, HgSTe, CdHgS, CdHgSe, CdHgTe, HgZnS, HgZnSe, HgZnTe, HgZnTeS, CdZnSeS, CdZnSeTe, CdZnSTe, CdHgSeS, CdHgSeTe, CdHgSTe, HgZnSeS, HgZnSeTe, HgZnSTe or a combination thereof. Preferably, the core of the quantum dot is ZnSeTe.

[0047] The shell layer covering the core body protects the core body and may include one or more shell layers. The energy band width of the shell layer material is greater than that of the core body. For example, the shell layer is CdZnSe, CdZnS, ZnSe, CdSe, ZnSeS, ZnS, CdS, etc., and combinations thereof.

[0048] In addition to the hydrophilicity of carbon dots, other quantum dots are usually directly synthesized and have excellent performance. The quantum dots are oily quantum dots (with organic acids, organic amines, organic phosphines, or thiols on the surface). Water-based quantum dots are formed only through additional ligand modification. Therefore, quantum dots usually refer to oily quantum dots, which have oily ligands. The oily ligands include: at least one of organic acids, organic amines, organic phosphines, or thiols. The organic acids include: at least one of dodecanoic acid, hexadecanoic acid, octadecanoic acid, oleic acid, undecylenic acid, tetradecylenic acid, stearic acid, or benzoic acid. The organic amines include: at least one of octylamine, oleylamine, dodecylamine, hexadecylamine, and octadecylamine. The organic phosphine includes: at least one of trioctylphosphine, trioctylphosphine oxide, tributylphosphine, and diphenylphosphine. The thiol includes: at least one of octanethiol, dodecanethiol, hexadecylthiol, octadecylthiol, or benzylthiol.

[0049] In some embodiments, the inorganic acid / acid includes at least one of hydrofluoric acid (also known as hydrogen fluoride), hydrogen chloride, sulfuric acid, formic acid, acetic acid, sodium fluoride, aluminum fluoride, calcium fluoride, lead tetrafluoride, phenylcarbonyl fluoride, tetrabutylammonium fluoride, fluoroacetamide, or sodium fluoroacetate.

[0050] By using inorganic acid / acid to etch the quantum dot core, the surface oxidation state of the quantum dot core is reduced, thereby improving the performance of the final quantum dot product; at the same time, the additional anions can also act as surface ligands to reduce the amount of carboxylic acid ligands on the surface of the quantum dots, which is beneficial to hole transport in QLEDs.

[0051] In some embodiments, the chloride consists of a metal element and a chlorine element.

[0052] Furthermore, the chloride includes at least one of zinc chloride, potassium chloride, sodium chloride, copper chloride, magnesium chloride, calcium chloride, ferric chloride, ferrous chloride, or aluminum chloride.

[0053] After the synthesis of the quantum dot core, the addition of chloride introduces Cl - Replacing some OA ligands can improve the thermal stability of the device and the injection / transfer efficiency of charges. Among all the ligands that can bind to Zn dangling bonds, Cl- binds more strongly to cation dangling bonds such as Zn, making the surface energy stable. DFT calculations show that the mid-band gap trap state close to the valence band maximum in the Zn-OA passivated surface is replaced by the addition of Cl - Elimination, which means that Cl - Replacing OA can improve the quantum yield of quantum dots.

[0054] After the quantum dot core is synthesized, adding inorganic acid / acid and chloride at the same time can greatly eliminate the stacking fault, thereby improving the photoinduced and electroinduced properties of the product. At the same time, there is a synergistic effect between inorganic acid / acid and chloride. Inorganic acid / acid can separate ligands by protonation, while chloride can replace the bulky fatty acid ligands to coordinate with the dangling bonds on the passivated surface.

[0055] In some embodiments, the electron transport material includes: metal oxide, core-shell structure metal oxide, element-doped metal oxide, element-doped core-shell structure metal oxide.

[0056] Furthermore, the metal oxide includes: at least one of zinc oxide, magnesium oxide, zinc magnesium oxide, aluminum oxide, and zinc aluminum oxide; the core-shell structured metal oxide includes: at least one of zinc magnesium oxide / magnesium oxide, zinc magnesium oxide / zinc oxide, zinc oxide / magnesium oxide, zinc aluminum oxide / magnesium oxide, zinc aluminum oxide / zinc oxide, zinc aluminum oxide / aluminum oxide, and zinc oxide / aluminum oxide; the metal oxide doped with elements or the core-shell structured metal oxide doped with elements is a metal oxide or a core-shell structured metal oxide doped with other elements, and the doping elements include: at least one of aluminum, lithium, tin, manganese, yttrium, lanthanum, copper, nickel, zirconium, cerium, and gadolinium.

[0057] Introducing Cl into electron transport materials - Ligands can replace part of the ligands on the surface of the electron transport material, reduce the steric hindrance effect of the ligands on the surface, and improve the spin coating film forming property. At the same time, the smaller steric hindrance effect of the ligands can increase the coverage of the ligands on the surface of the electron transport material and improve its stability.

[0058] In QLED devices, the surface of the quantum dot core is covered with Cl - By replacing some OA ligands and passivating them, the electron transport material is also - Ligand coordination and passivation, while using Cl - There is a synergistic effect between the passivated quantum dots and the electron transport material, which significantly promotes the injection, transmission and recombination of charges between the quantum dot light-emitting layer and the electron transport layer, promotes the occurrence of radiative recombination, and significantly improves the life of the QLED device composed of the two. - The QLED device made of passivated quantum dots and electron transport materials can achieve LT50@1000nits for more than 60h, while the QLED device made of un-Cl - The QLED device made of passivated quantum dots and electron transport materials has a LT50@1000nits of less than 5h. - Passivated quantum dots are used to prepare QLED devices, or Cl is used alone - The lifetime of QLED devices made with passivated electron transport materials is significantly less than 60h.

[0059] The organic solvent for preparing the electron transport material may be a solvent known in the art, such as ethanol, methanol, isopropanol, butanol, etc., which is not specifically limited here.

[0060] In some embodiments, the cathode material includes at least one of aluminum, magnesium, calcium, silver and alloys thereof. The cathode has a thickness of 20-200 nm.

[0061] The second aspect of the present application provides a method for preparing a long-life electroluminescent device, the method comprising: sequentially arranging a hole injection layer, a hole transport layer, a quantum dot light-emitting layer, and an electron transport layer on an anode substrate, and forming a cathode layer or a packaged cathode plate on the electron transport layer to obtain an electroluminescent device; wherein,

[0062] The quantum dot light-emitting layer includes quantum dots, after synthesizing the quantum dot core body, adding inorganic acid / acid and chloride to etch and passivate it, and then synthesizing the shell layer covering the core body;

[0063] The electron transport layer includes an electron transport material. When synthesizing the electron transport material, chloride is added to passivate it to form Cl - Passivated electron transport materials.

[0064] In some embodiments, the inorganic acid is added in a molar ratio of 1:(200-5000) to the acid and chloride.

[0065] Furthermore, the inorganic acid is added in a molar ratio of 1:(500-2000) to the chloride.

[0066] In an organic solvent, a cation precursor and an anion precursor are added to prepare a core; then an inorganic acid / acid and chloride are added for etching and passivation; finally, a cation precursor and anion precursor required for preparing a shell are added. For example, the organic solvent includes: at least one of trioctylamine (TOA), hexadecylamine, dioctylamine, hexadecane, octadecane, squalane, phenyldodecane, phenyltetradecane, and phenylhexadecane. The selenium precursor includes: at least one of selenium-trioctylphosphine (Se-TOP), selenium-tributylphosphine (Se-TBP), selenium-triphenylphosphine (Se-TPP), and selenium-diphenylphosphine (Se-DPP). The tellurium precursor includes: at least one of tellurium-trioctylphosphine (Te-TOP), tellurium-tributylphosphine (Te-TBP), and tellurium-triphenylphosphine (Te-TPP). The zinc precursor includes: Zn powder, ZnO, and alkylated Zn compounds, and the alkylated Zn compounds include: at least one of C2-C30 dialkyl zinc, Zn alkoxide, Zn carboxylate, Zn nitrate, Zn perchlorate, Zn sulfate, Zn acetylacetonate, Zn halide, Zn cyanide, Zn hydroxide, zinc carbonate, and zinc peroxide. The zinc precursor includes: at least one of dimethyl zinc, diethyl zinc, zinc acetate, zinc acetylacetonate, zinc iodide, zinc bromide, zinc chloride, zinc fluoride, zinc carbonate, zinc cyanide, zinc nitrate, zinc oxide, zinc oleate, zinc peroxide, zinc perchlorate, zinc palmitate, zinc laurate, zinc n-hexanoate, and zinc sulfate. The sulfur precursor includes at least one of hexanethiol, octylthiol, decanethiol, dodecanethiol, hexadecanethiol, mercaptopropylsilane, sulfur-trioctylphosphine (S-TOP), sulfur-tributylphosphine (S-TBP), sulfur-triphenylphosphine (S-TPP), sulfur-trioctylamine (S-TOA), bis(trimethylsilyl)sulfide, ammonium sulfide, and sodium sulfide.

[0067] Furthermore, the diameter of the core is 4.0-4.5 nm, and the thickness of the shell is 2.4-3.5 nm.

[0068] The quantum dots are mixed with an organic solvent (such as n-octane), and the quantum dots are diluted to a desired concentration using the organic solvent to prepare a quantum dot light-emitting layer.

[0069] In some embodiments, when the electron transport material is a metal oxide or a metal oxide doped with elements, the chloride is added after the metal oxide or the metal oxide doped with elements is synthesized; when the electron transport material is a core-shell structure metal oxide or a core-shell structure metal oxide doped with elements, the core-shell structure metal oxide or the core-shell structure metal oxide doped with elements comprises an oxide core and an oxide shell layer covering the oxide core, and after the oxide core is synthesized, the chloride is added, and then the oxide shell layer is synthesized.

[0070] The electron transport layer can be prepared by mixing the electron transport material with an alcohol solvent (such as ethanol) and diluting the electron transport material to a desired concentration using the alcohol solvent.

[0071] The present invention will be further described in detail below in conjunction with specific embodiments and comparative examples, but the present invention is not limited to the following embodiments. The implementation conditions used in the embodiments can be further adjusted according to different requirements of specific use, and the unspecified conditions are conventional conditions in the industry.

[0072] Embodiment 1:

[0073] Preparation of Cl - Passivated blue light ZnSeTe / ZnSe / ZnSeS / ZnS quantum dots:

[0074] In a 250mL three-necked flask, add 1.02g palmitic acid (PA, 4mMol / L), 5mL oleylamine (OlAm), 20mL trioctylamine (TOA), evacuate, heat to 120℃, and maintain vacuum for 2h; introduce Ar, set the reaction temperature to 240℃, and start heating. When the temperature reaches 240℃, add 1mL diphenylphosphine (DPP), 0.6mL selenium-trioctylphosphine (Se-TOP, 2Mol / L), 0.5mL tellurium-trioctylphosphine (Te-TOP, 0.1Mol / L), diethylzinc (DEZ, 1Mol / L), react for 30min, and form blue light ZnSeTe nuclei. Add 0.1 mL of hydrofluoric acid-acetone solution (HF-acetone, 10% HF, 90% acetone) and 0.5 mL of ZnCl2 / OlAm (0.5 Mol / L) into the reaction system (i.e., a three-necked flask, the same below) and react for 1 min.

[0075] The temperature was raised to 310°C, and 20 mL of zinc oleate (Zn(OA)2, 0.71 Mol / L), 5 mL of selenium-trioctylphosphine (Se-TOP, 2 Mol / L), and 10 mL of zinc oleate (Zn(OA)2, 0.71 Mol / L) were added to form a ZnSe transition layer and obtain a ZnSeTe / ZnSe core-shell structure.

[0076] 10 mL of zinc oleate (Zn(OA)2, 0.71 Mol / L) was added to the reaction system; the temperature was raised to 330°C, 4 mL of sulfur-trioctylphosphine (S-TOP, 2 Mol / L) and 10 mL of zinc oleate (Zn(OA)2, 0.71 Mol / L) were added to form a ZnSeS transition layer to obtain a ZnSeTe / ZnSe / ZnSeS core-shell structure.

[0077] Cool down to 250℃, add 24mL oleylamine zinc (Zn / OlAm, 0.4Mol / L), 6mL sulfur-trioctylphosphine (S-TOP, 2Mol / L), 8mL oleylamine zinc (Zn / OlAm, 0.4Mol / L), 1mL n-dodecyl mercaptan (DDT) to the reaction system. After the reaction is completed, stop heating and let the reaction solution cool to room temperature. Form a ZnS shell layer and obtain Cl - Passivated blue light ZnSeTe / ZnSe / ZnSeS / ZnS quantum dots.

[0078] Preparation of Cl - Passivated ZnMgO / MgO:

[0079] Preparation of solution A: In a 100 ml three-necked flask, add 0.77 g of Zn(OAc)2, 0.064 g of Mg(OAc)2 and 10 ml of DMSO, and stir at 20°C to dissolve. Preparation of solution B: In a 50 ml three-necked flask, add 0.56 g of TMAH and 10 ml of ethanol, and stir at 20°C to dissolve. Quickly pour solution B into solution A, maintain the temperature at 20°C, and continue stirring for 90 minutes to obtain ZnMgO core.

[0080] Add 0.136 g of ZnCl2 to a 100 ml three-necked flask and stir for 20 min. Then add 0.1 g of Mg(OAc)2 and ultrasonicate for 20 min to obtain Cl - Passivated ZnMgO / MgO.

[0081] Preparation of electroluminescent devices:

[0082] Prepare 16 mg / mL of the above Cl - The n-octane solution of the passivated blue light ZnSeTe / ZnSe / ZnSeS / ZnS quantum dots was prepared for use; 20 mg / mL of the above Cl - The passivated ZnMgO / MgO ethanol solution is set aside.

[0083] A polyethylenedioxythiophene-poly(styrene sulfonate) layer (PEDOT:PSS layer, hole injection layer) and a poly(9,9-dioctylfluorene-CO-N-(4-butylphenyl)diphenylamine) layer (TFB, hole transport layer) were sequentially prepared on indium tin oxide glass (anode);

[0084] Spin-coat the above-mentioned Cl - The n-octane solution of the passivated blue light ZnSeTe / ZnSe / ZnSeS / ZnS quantum dots is dried to obtain a quantum dot light-emitting layer;

[0085] Spin coat the above Cl on the quantum dot light emitting layer -The passivated ZnMgO / MgO ethanol solution is dried to obtain an electron transport layer; an Al electrode is prepared on the electron transport layer, and encapsulated to obtain a blue light QLED device.

[0086] Embodiment 2:

[0087] Preparation of Cl - Passivated green ZnSeTe / ZnSe / ZnSeS / ZnS quantum dots:

[0088] In a 250mL three-necked flask, add 1ml oleic acid, 2mL oleylamine, 15mL trioctylamine, evacuate, heat to 120℃, and keep the vacuum state for 2h; introduce Ar, set the reaction temperature to 240℃, and start heating. When the temperature reaches 240℃, add 1.76mL zinc hexanoate (1Mol / L), 0.4mL selenium-diphenylphosphine (Se-DPP, 2Mol / L), 2.4mL tellurium-trioctylphosphine (Te-TOP, 0.1Mol / L), react for 20min to form green light ZnSeTe nuclei. Add 0.1mL hydrofluoric acid-acetone solution (HF-acetone, 10% HF, 90% acetone) and 0.5mL ZnCl2 / OlAm (0.5Mol / L) to the reaction system (i.e., in the three-necked flask, the same below), and react for 1min.

[0089] The temperature was raised to 310°C, and 10 mL of zinc oleate (Zn(OA)2, 0.71 Mol / L), 1.5 mL of selenium-trioctylphosphine (Se-TOP, 2 Mol / L), and 6 mL of zinc oleate (Zn(OA)2, 0.71 Mol / L) were added to form a ZnSe transition layer and obtain a ZnSeTe / ZnSe core-shell structure.

[0090] 1.5 mL of a mixed solution of S-TOP and Se-TOP (S-TOP 2 Mol / L, Se-TOP 2 Mol / L, volume ratio of 1:1) and 6 mL of zinc oleate (Zn(OA)2, 0.71 Mol / L) were added to the reaction system to form a ZnSeS transition layer and obtain a ZnSeTe / ZnSe / ZnSeS core-shell structure.

[0091] Cool down to 250℃, add 16mL zinc oleylamine (Zn / OlAm, 0.4Mol / L) and 4mL sulfur-trioctylphosphine (S-TOP, 2Mol / L) to the reaction system. After the reaction is completed, stop heating and let the reaction solution cool to room temperature. Form a ZnS shell layer and obtain Cl - Passivated green light emitting ZnSeTe / ZnSe / ZnSeS / ZnS quantum dots.

[0092] Preparation of Cl - Passivated ZnMgO:

[0093] Preparation of solution A: In a 100 ml three-necked flask, add 0.77 g of Zn(OAc)2, 0.064 g of Mg(OAc)2 and 10 ml of DMSO, and stir at 20°C to dissolve. Preparation of solution B: In a 50 ml three-necked flask, add 0.56 g of TMAH and 10 ml of ethanol, and stir at 20°C to dissolve. Quickly pour solution B into solution A, maintain the temperature at 20°C, and continue stirring for 90 min to obtain ZnMgO.

[0094] Add 0.136 g of ZnCl2 to a 100 ml three-necked flask and stir for 20 min to obtain Cl - Passivated ZnMgO.

[0095] Preparation of electroluminescent devices:

[0096] Prepare 16 mg / mL of the above Cl - The n-octane solution of the passivated green light ZnSeTe / ZnSe / ZnSeS / ZnS quantum dots was prepared for use; 20 mg / mL of the above Cl - The passivated ZnMgO ethanol solution is set aside.

[0097] A polyethylenedioxythiophene-poly(styrene sulfonate) layer (PEDOT:PSS layer, hole injection layer) and a poly(9,9-dioctylfluorene-CO-N-(4-butylphenyl)diphenylamine) layer (TFB, hole transport layer) were sequentially prepared on indium tin oxide glass (anode);

[0098] Spin-coat the above-mentioned Cl - The n-octane solution of the passivated green light ZnSeTe / ZnSe / ZnSeS / ZnS quantum dots is dried to obtain a quantum dot light-emitting layer;

[0099] Spin coat the above Cl on the quantum dot light emitting layer - The passivated ZnMgO ethanol solution is dried to obtain an electron transport layer; an Al electrode is prepared on the electron transport layer, and encapsulated to obtain a green light QLED device.

[0100] Comparative Example 1:

[0101] Preparation of blue light ZnSeTe / ZnSe / ZnSeS / ZnS quantum dots:

[0102] In a 250mL three-necked flask, add 1.02g palmitic acid (PA, 4mMol / L), 5mL oleylamine (OlAm), 20mL trioctylamine (TOA), evacuate, heat to 120℃, and keep the vacuum state for 2h; introduce Ar, set the reaction temperature to 240℃, and start heating. When the temperature reaches 240℃, add 1mL diphenylphosphine (DPP), 0.6mL selenium-trioctylphosphine (Se-TOP, 2Mol / L), 0.5mL tellurium-trioctylphosphine (Te-TOP, 0.1Mol / L), diethylzinc (DEZ, 1Mol / L), react for 30min to form blue light ZnSeTe nuclei. Add 0.1mL hydrofluoric acid-acetone solution (HF-acetone, 10% HF, 90% acetone) to the reaction system (i.e., in the three-necked flask, the same below) and react for 1min.

[0103] The temperature was raised to 310°C, and 20 mL of zinc oleate (Zn(OA)2, 0.71 Mol / L), 5 mL of selenium-trioctylphosphine (Se-TOP, 2 Mol / L), and 10 mL of zinc oleate (Zn(OA)2, 0.71 Mol / L) were added to form a ZnSe transition layer and obtain a ZnSeTe / ZnSe core-shell structure.

[0104] 10 mL of zinc oleate (Zn(OA)2, 0.71 Mol / L) was added to the reaction system; the temperature was raised to 330°C, 4 mL of sulfur-trioctylphosphine (S-TOP, 2 Mol / L) and 10 mL of zinc oleate (Zn(OA)2, 0.71 Mol / L) were added to form a ZnSeS transition layer to obtain a ZnSeTe / ZnSe / ZnSeS core-shell structure.

[0105] Cool down to 250℃, add 24mL oleylamine zinc (Zn / OlAm, 0.4Mol / L), 6mL sulfur-trioctylphosphine (S-TOP, 2Mol / L), 8mL oleylamine zinc (Zn / OlAm, 0.4Mol / L), 1mL n-dodecyl mercaptan (DDT) to the reaction system. After the reaction is completed, stop heating and let the reaction solution cool to room temperature. Form a ZnS shell layer and obtain blue light

[0106] ZnSeTe / ZnSe / ZnSeS / ZnS quantum dots.

[0107] Preparation of ZnMgO / MgO:

[0108] Preparation of solution A: In a 100 ml three-necked flask, add 0.77 g of Zn(OAc)2, 0.064 g of Mg(OAc)2 and 10 ml of DMSO, and stir at 20°C to dissolve. Preparation of solution B: In a 50 ml three-necked flask, add 0.56 g of TMAH and 10 ml of ethanol, and stir at 20°C to dissolve. Quickly pour solution B into solution A, maintain the temperature at 20°C, and continue stirring for 90 minutes to obtain ZnMgO core.

[0109] Into a 100 ml three-necked flask, add 0.1 g of Mg(OAc)2 and ultrasonicate for 20 min to obtain ZnMgO / MgO.

[0110] Preparation of electroluminescent devices:

[0111] A 16 mg / mL n-octane solution of the above-mentioned blue light ZnSeTe / ZnSe / ZnSeS / ZnS quantum dots was prepared for later use; and a 20 mg / mL ethanol solution of the above-mentioned ZnMgO / MgO was prepared for later use.

[0112] A polyethylenedioxythiophene-poly(styrene sulfonate) layer (PEDOT:PSS layer, hole injection layer) and a poly(9,9-dioctylfluorene-CO-N-(4-butylphenyl)diphenylamine) layer (TFB, hole transport layer) were sequentially prepared on indium tin oxide glass (anode);

[0113] Spin coating the n-octane solution containing the above-mentioned blue light ZnSeTe / ZnSe / ZnSeS / ZnS quantum dots on the TFB layer, and drying to obtain a quantum dot light-emitting layer;

[0114] The above ZnMgO / MgO ethanol solution is spin-coated on the quantum dot light-emitting layer and dried to obtain an electron transport layer; an Al electrode is prepared on the electron transport layer and encapsulated to obtain a blue light QLED device.

[0115] Comparative Example 2:

[0116] Preparation of Cl - Passivated blue light ZnSeTe / ZnSe / ZnSeS / ZnS quantum dots:

[0117] In a 250mL three-necked flask, add 1.02g palmitic acid (PA, 4mMol / L), 5mL oleylamine (OlAm), 20mL trioctylamine (TOA), evacuate, heat to 120℃, and maintain vacuum for 2h; introduce Ar, set the reaction temperature to 240℃, and start heating. When the temperature reaches 240℃, add 1mL diphenylphosphine (DPP), 0.6mL selenium-trioctylphosphine (Se-TOP, 2Mol / L), 0.5mL tellurium-trioctylphosphine (Te-TOP, 0.1Mol / L), diethylzinc (DEZ, 1Mol / L), react for 30min, and form blue light ZnSeTe nuclei. Add 0.1 mL of hydrofluoric acid-acetone solution (HF-acetone, 10% HF, 90% acetone) and 0.5 mL of ZnCl2 / OlAm (0.5 Mol / L) into the reaction system (i.e., a three-necked flask, the same below) and react for 1 min.

[0118] The temperature was raised to 310°C, and 20 mL of zinc oleate (Zn(OA)2, 0.71 Mol / L), 5 mL of selenium-trioctylphosphine (Se-TOP, 2 Mol / L), and 10 mL of zinc oleate (Zn(OA)2, 0.71 Mol / L) were added to form a ZnSe transition layer and obtain a ZnSeTe / ZnSe core-shell structure.

[0119] 10 mL of zinc oleate (Zn(OA)2, 0.71 Mol / L) was added to the reaction system; the temperature was raised to 330°C, 4 mL of sulfur-trioctylphosphine (S-TOP, 2 Mol / L) and 10 mL of zinc oleate (Zn(OA)2, 0.71 Mol / L) were added to form a ZnSeS transition layer to obtain a ZnSeTe / ZnSe / ZnSeS core-shell structure.

[0120] Cool down to 250℃, add 24mL oleylamine zinc (Zn / OlAm, 0.4Mol / L), 6mL sulfur-trioctylphosphine (S-TOP, 2Mol / L), 8mL oleylamine zinc (Zn / OlAm, 0.4Mol / L), 1mL n-dodecyl mercaptan (DDT) to the reaction system. After the reaction is completed, stop heating and let the reaction solution cool to room temperature. Form a ZnS shell layer and obtain Cl - Passivated blue light ZnSeTe / ZnSe / ZnSeS / ZnS quantum dots.

[0121] Preparation of ZnMgO / MgO:

[0122] Preparation of solution A: In a 100 ml three-necked flask, add 0.77 g of Zn(OAc)2, 0.064 g of Mg(OAc)2 and 10 ml of DMSO, and stir at 20°C to dissolve. Preparation of solution B: In a 50 ml three-necked flask, add 0.56 g of TMAH and 10 ml of ethanol, and stir at 20°C to dissolve. Quickly pour solution B into solution A, maintain the temperature at 20°C, and continue stirring for 90 minutes to obtain ZnMgO core.

[0123] Into a 100 ml three-necked flask, add 0.1 g of Mg(OAc)2 and ultrasonicate for 20 min to obtain ZnMgO / MgO.

[0124] Preparation of electroluminescent devices:

[0125] Prepare 16 mg / mL of the above Cl - The n-octane solution of the passivated blue light ZnSeTe / ZnSe / ZnSeS / ZnS quantum dots is prepared for later use; and a 20 mg / mL ethanol solution of the above ZnMgO / MgO is prepared for later use.

[0126] A polyethylenedioxythiophene-poly(styrene sulfonate) layer (PEDOT:PSS layer, hole injection layer) and a poly(9,9-dioctylfluorene-CO-N-(4-butylphenyl)diphenylamine) layer (TFB, hole transport layer) were sequentially prepared on indium tin oxide glass (anode);

[0127] Spin-coat the above-mentioned Cl - The n-octane solution of the passivated blue light ZnSeTe / ZnSe / ZnSeS / ZnS quantum dots is dried to obtain a quantum dot light-emitting layer;

[0128] The above ZnMgO / MgO ethanol solution is spin-coated on the quantum dot light-emitting layer and dried to obtain an electron transport layer; an Al electrode is prepared on the electron transport layer and encapsulated to obtain a blue light QLED device.

[0129] Comparative Example 3:

[0130] Preparation of blue light ZnSeTe / ZnSe / ZnSeS / ZnS quantum dots:

[0131] In a 250mL three-necked flask, add 1.02g palmitic acid (PA, 4mMol / L), 5mL oleylamine (OlAm), 20mL trioctylamine (TOA), evacuate, heat to 120℃, and keep the vacuum state for 2h; introduce Ar, set the reaction temperature to 240℃, and start heating. When the temperature reaches 240℃, add 1mL diphenylphosphine (DPP), 0.6mL selenium-trioctylphosphine (Se-TOP, 2Mol / L), 0.5mL tellurium-trioctylphosphine (Te-TOP, 0.1Mol / L), diethylzinc (DEZ, 1Mol / L), react for 30min to form blue light ZnSeTe nuclei. Add 0.1mL hydrofluoric acid-acetone solution (HF-acetone, 10% HF, 90% acetone) to the reaction system (i.e., in the three-necked flask, the same below) and react for 1min.

[0132] The temperature was raised to 310°C, and 20 mL of zinc oleate (Zn(OA)2, 0.71 Mol / L), 5 mL of selenium-trioctylphosphine (Se-TOP, 2 Mol / L), and 10 mL of zinc oleate (Zn(OA)2, 0.71 Mol / L) were added to form a ZnSe transition layer and obtain a ZnSeTe / ZnSe core-shell structure.

[0133] 10 mL of zinc oleate (Zn(OA)2, 0.71 Mol / L) was added to the reaction system; the temperature was raised to 330°C, 4 mL of sulfur-trioctylphosphine (S-TOP, 2 Mol / L) and 10 mL of zinc oleate (Zn(OA)2, 0.71 Mol / L) were added to form a ZnSeS transition layer to obtain a ZnSeTe / ZnSe / ZnSeS core-shell structure.

[0134] Cool down to 250℃, add 24mL oleylamine zinc (Zn / OlAm, 0.4Mol / L), 6mL sulfur-trioctylphosphine (S-TOP, 2Mol / L), 8mL oleylamine zinc (Zn / OlAm, 0.4Mol / L), 1mL n-dodecyl mercaptan (DDT) to the reaction system. After the reaction is completed, stop heating and let the reaction solution cool to room temperature. Form a ZnS shell layer and obtain blue light

[0135] ZnSeTe / ZnSe / ZnSeS / ZnS quantum dots.

[0136] Preparation of Cl - Passivated ZnMgO / MgO:

[0137] Preparation of solution A: In a 100 ml three-necked flask, add 0.77 g of Zn(OAc)2, 0.064 g of Mg(OAc)2 and 10 ml of DMSO, and stir at 20°C to dissolve. Preparation of solution B: In a 50 ml three-necked flask, add 0.56 g of TMAH and 10 ml of ethanol, and stir at 20°C to dissolve. Quickly pour solution B into solution A, maintain the temperature at 20°C, and continue stirring for 90 minutes to obtain ZnMgO core.

[0138] Add 0.136 g of ZnCl2 to a 100 ml three-necked flask and stir for 20 min. Then add 0.1 g of Mg(OAc)2 and ultrasonicate for 20 min to obtain Cl - Passivated ZnMgO / MgO.

[0139] Preparation of electroluminescent devices:

[0140] Prepare 16 mg / mL of the above blue light ZnSeTe / ZnSe / ZnSeS / ZnS quantum dots in n-octane for later use; prepare 20 mg / mL of the above Cl - The passivated ZnMgO / MgO ethanol solution is set aside.

[0141] A polyethylenedioxythiophene-poly(styrene sulfonate) layer (PEDOT:PSS layer, hole injection layer) and a poly(9,9-dioctylfluorene-CO-N-(4-butylphenyl)diphenylamine) layer (TFB, hole transport layer) were sequentially prepared on indium tin oxide glass (anode);

[0142] Spin coating the n-octane solution containing the above-mentioned blue light ZnSeTe / ZnSe / ZnSeS / ZnS quantum dots on the TFB layer, and drying to obtain a quantum dot light-emitting layer;

[0143] Spin coat the above Cl on the quantum dot light emitting layer - The passivated ZnMgO / MgO ethanol solution is dried to obtain an electron transport layer; an Al electrode is prepared on the electron transport layer, and encapsulated to obtain a blue light QLED device.

[0144] Comparative Example 4:

[0145] Preparation of green light ZnSeTe / ZnSe / ZnSeS / ZnS quantum dots:

[0146] In a 250mL three-necked flask, add 1ml oleic acid, 2ml oleylamine, 15ml trioctylamine, evacuate, heat to 120℃, keep vacuum for 2h; introduce Ar, set the reaction temperature to 240℃, and start heating. When the temperature reaches 240℃, add 1.76ml zinc hexanoate (1mol / L), 0.4ml selenium-diphenylphosphine (Se-DPP, 2mol / L), 2.4ml tellurium-trioctylphosphine (Te-TOP, 0.1mol / L), react for 20min to form green light ZnSeTe nuclei. Add 0.1ml hydrofluoric acid-acetone solution (HF-acetone, 10% HF, 90% acetone) to the reaction system (i.e., in the three-necked flask, the same below) and react for 1min.

[0147] The temperature was raised to 310°C, and 10 mL of zinc oleate (Zn(OA)2, 0.71 Mol / L), 1.5 mL of selenium-trioctylphosphine (Se-TOP, 2 Mol / L), and 6 mL of zinc oleate (Zn(OA)2, 0.71 Mol / L) were added to form a ZnSe transition layer and obtain a ZnSeTe / ZnSe core-shell structure.

[0148] 1.5 mL of a mixed solution of S-TOP and Se-TOP (S-TOP 2 Mol / L, Se-TOP 2 Mol / L, volume ratio of 1:1) and 6 mL of zinc oleate (Zn(OA)2, 0.71 Mol / L) were added to the reaction system to form a ZnSeS transition layer and obtain a ZnSeTe / ZnSe / ZnSeS core-shell structure.

[0149] Cool down to 250℃, add 16mL zinc oleylamine (Zn / OlAm, 0.4Mol / L) and 4mL sulfur-trioctylphosphine (S-TOP, 2Mol / L) to the reaction system. After the reaction is completed, stop heating and let the reaction solution cool to room temperature. Form a ZnS shell layer and obtain Cl - Passivated green light emitting ZnSeTe / ZnSe / ZnSeS / ZnS quantum dots.

[0150] Preparation of ZnMgO:

[0151] Preparation of solution A: In a 100 ml three-necked flask, add 0.77 g of Zn(OAc)2, 0.064 g of Mg(OAc)2 and 10 ml of DMSO, and stir at 20°C to dissolve. Preparation of solution B: In a 50 ml three-necked flask, add 0.56 g of TMAH and 10 ml of ethanol, and stir at 20°C to dissolve. Quickly pour solution B into solution A, maintain the temperature at 20°C, and continue stirring for 90 min to obtain ZnMgO.

[0152] Preparation of electroluminescent devices:

[0153] A 16 mg / mL n-octane solution of the green light ZnSeTe / ZnSe / ZnSeS / ZnS quantum dots was prepared for later use; and a 20 mg / mL ethanol solution of the ZnMgO was prepared for later use.

[0154] A polyethylenedioxythiophene-poly(styrene sulfonate) layer (PEDOT:PSS layer, hole injection layer) and a poly(9,9-dioctylfluorene-CO-N-(4-butylphenyl)diphenylamine) layer (TFB, hole transport layer) were sequentially prepared on indium tin oxide glass (anode);

[0155] Spin coating the n-octane solution containing the green light ZnSeTe / ZnSe / ZnSeS / ZnS quantum dots on the TFB layer, and drying to obtain a quantum dot light-emitting layer;

[0156] The above ZnMgO ethanol solution is spin-coated on the quantum dot light-emitting layer and dried to obtain an electron transport layer; an Al electrode is prepared on the electron transport layer and packaged to obtain a green light QLED device.

[0157] Comparative Example 5:

[0158] Preparation of Cl - Passivated green ZnSeTe / ZnSe / ZnSeS / ZnS quantum dots:

[0159] In a 250mL three-necked flask, add 1ml oleic acid, 2mL oleylamine, 15mL trioctylamine, evacuate, heat to 120℃, and keep the vacuum state for 2h; introduce Ar, set the reaction temperature to 240℃, and start heating. When the temperature reaches 240℃, add 1.76mL zinc hexanoate (1Mol / L), 0.4mL selenium-diphenylphosphine (Se-DPP, 2Mol / L), 2.4mL tellurium-trioctylphosphine (Te-TOP, 0.1Mol / L), react for 20min to form green light ZnSeTe nuclei. Add 0.1mL hydrofluoric acid-acetone solution (HF-acetone, 10% HF, 90% acetone) and 0.5mL ZnCl2 / OlAm (0.5Mol / L) to the reaction system (i.e., in the three-necked flask, the same below), and react for 1min.

[0160] The temperature was raised to 310°C, and 10 mL of zinc oleate (Zn(OA)2, 0.71 Mol / L), 1.5 mL of selenium-trioctylphosphine (Se-TOP, 2 Mol / L), and 6 mL of zinc oleate (Zn(OA)2, 0.71 Mol / L) were added to form a ZnSe transition layer and obtain a ZnSeTe / ZnSe core-shell structure.

[0161] 1.5 mL of a mixed solution of S-TOP and Se-TOP (S-TOP 2 Mol / L, Se-TOP 2 Mol / L, volume ratio of 1:1) and 6 mL of zinc oleate (Zn(OA)2, 0.71 Mol / L) were added to the reaction system to form a ZnSeS transition layer and obtain a ZnSeTe / ZnSe / ZnSeS core-shell structure.

[0162] Cool down to 250℃, add 16mL zinc oleylamine (Zn / OlAm, 0.4Mol / L) and 4mL sulfur-trioctylphosphine (S-TOP, 2Mol / L) to the reaction system. After the reaction is completed, stop heating and let the reaction solution cool to room temperature. Form a ZnS shell layer and obtain Cl - Passivated green light emitting ZnSeTe / ZnSe / ZnSeS / ZnS quantum dots.

[0163] Preparation of ZnMgO:

[0164] Preparation of solution A: In a 100 ml three-necked flask, add 0.77 g of Zn(OAc)2, 0.064 g of Mg(OAc)2 and 10 ml of DMSO, and stir at 20°C to dissolve. Preparation of solution B: In a 50 ml three-necked flask, add 0.56 g of TMAH and 10 ml of ethanol, and stir at 20°C to dissolve. Quickly pour solution B into solution A, maintain the temperature at 20°C, and continue stirring for 90 min to obtain ZnMgO.

[0165] Preparation of electroluminescent devices:

[0166] Prepare 16 mg / mL of the above Cl - The n-octane solution of the passivated green light ZnSeTe / ZnSe / ZnSeS / ZnS quantum dots is prepared for later use; and a 20 mg / mL ethanol solution of the above ZnMgO is prepared for later use.

[0167] A polyethylenedioxythiophene-poly(styrene sulfonate) layer (PEDOT:PSS layer, hole injection layer) and a poly(9,9-dioctylfluorene-CO-N-(4-butylphenyl)diphenylamine) layer (TFB, hole transport layer) were sequentially prepared on indium tin oxide glass (anode);

[0168] Spin-coat the above-mentioned Cl - The n-octane solution of the passivated green light ZnSeTe / ZnSe / ZnSeS / ZnS quantum dots is dried to obtain a quantum dot light-emitting layer;

[0169] The above ZnMgO ethanol solution is spin-coated on the quantum dot light-emitting layer and dried to obtain an electron transport layer; an Al electrode is prepared on the electron transport layer and packaged to obtain a green light QLED device.

[0170] Comparative Example 6:

[0171] Preparation of green light ZnSeTe / ZnSe / ZnSeS / ZnS quantum dots:

[0172] In a 250mL three-necked flask, add 1ml oleic acid, 2ml oleylamine, 15ml trioctylamine, evacuate, heat to 120℃, keep vacuum for 2h; introduce Ar, set the reaction temperature to 240℃, and start heating. When the temperature reaches 240℃, add 1.76ml zinc hexanoate (1mol / L), 0.4ml selenium-diphenylphosphine (Se-DPP, 2mol / L), 2.4ml tellurium-trioctylphosphine (Te-TOP, 0.1mol / L), react for 20min to form green light ZnSeTe nuclei. Add 0.1ml hydrofluoric acid-acetone solution (HF-acetone, 10% HF, 90% acetone) to the reaction system (i.e., in the three-necked flask, the same below) and react for 1min.

[0173] The temperature was raised to 310°C, and 10 mL of zinc oleate (Zn(OA)2, 0.71 Mol / L), 1.5 mL of selenium-trioctylphosphine (Se-TOP, 2 Mol / L), and 6 mL of zinc oleate (Zn(OA)2, 0.71 Mol / L) were added to form a ZnSe transition layer and obtain a ZnSeTe / ZnSe core-shell structure.

[0174] 1.5 mL of a mixed solution of S-TOP and Se-TOP (S-TOP 2 Mol / L, Se-TOP 2 Mol / L, volume ratio of 1:1) and 6 mL of zinc oleate (Zn(OA)2, 0.71 Mol / L) were added to the reaction system to form a ZnSeS transition layer and obtain a ZnSeTe / ZnSe / ZnSeS core-shell structure.

[0175] Cool down to 250℃, add 16mL zinc oleylamine (Zn / OlAm, 0.4Mol / L) and 4mL sulfur-trioctylphosphine (S-TOP, 2Mol / L) to the reaction system. After the reaction is completed, stop heating and let the reaction solution cool to room temperature. Form a ZnS shell layer and obtain Cl - Passivated green light emitting ZnSeTe / ZnSe / ZnSeS / ZnS quantum dots.

[0176] Preparation of Cl - Passivated ZnMgO:

[0177] Preparation of solution A: In a 100 ml three-necked flask, add 0.77 g of Zn(OAc)2, 0.064 g of Mg(OAc)2 and 10 ml of DMSO, and stir at 20°C to dissolve. Preparation of solution B: In a 50 ml three-necked flask, add 0.56 g of TMAH and 10 ml of ethanol, and stir at 20°C to dissolve. Quickly pour solution B into solution A, maintain the temperature at 20°C, and continue stirring for 90 min to obtain ZnMgO.

[0178] Add 0.136 g of ZnCl2 to a 100 ml three-necked flask and continue stirring for 20 min to obtain Cl - Passivated ZnMgO.

[0179] Preparation of electroluminescent devices:

[0180] Prepare 16 mg / mL of the above green light ZnSeTe / ZnSe / ZnSeS / ZnS quantum dots in n-octane for later use; prepare 20 mg / mL of the above Cl - The passivated ZnMgO ethanol solution is set aside.

[0181] A polyethylenedioxythiophene-poly(styrene sulfonate) layer (PEDOT:PSS layer, hole injection layer) and a poly(9,9-dioctylfluorene-CO-N-(4-butylphenyl)diphenylamine) layer (TFB, hole transport layer) were sequentially prepared on indium tin oxide glass (anode);

[0182] Spin coating the n-octane solution containing the green light ZnSeTe / ZnSe / ZnSeS / ZnS quantum dots on the TFB layer, and drying to obtain a quantum dot light-emitting layer;

[0183] Spin coat the above Cl on the quantum dot light emitting layer - The passivated ZnMgO ethanol solution is dried to obtain an electron transport layer; an Al electrode is prepared on the electron transport layer, and encapsulated to obtain a green light QLED device.

[0184] The QLED devices prepared in Examples 1-2 and Comparative Examples 1-6 were respectively tested using a Spectra Scan PR-655 instrument for their electroluminescent maximum emission peak wavelength (EL), current density at 4 V voltage (J@4V), current efficiency at 2000 nits (CE@2000nits), external quantum efficiency at 2000 nits (EQE@2000nits), brightness at 4 V voltage (L@4V) and T50 lifetime at 1000 nits. The test results are shown in Table 1.

[0185] Table 1: Electroluminescent performance test results of embodiments and comparative examples.

[0186]

[0187] As can be seen from Table 1, compared with Comparative Examples 1-6, the current density, current efficiency, external quantum efficiency and brightness of the QLED devices in Examples 1-2 are significantly improved, especially the life of the QLED devices is significantly improved.

[0188] Although the present application has disclosed multiple aspects and embodiments, other aspects and embodiments will be obvious to those skilled in the art, and several modifications and improvements may be made without departing from the concept of the present application, all of which belong to the protection scope of the present application. The multiple aspects and embodiments disclosed in the present application are only for illustration and are not intended to limit the present application. The actual protection scope of the present application shall be subject to the claims.

Claims

1. A long-life electroluminescent device, comprising an anode substrate, a hole injection / transport layer, a quantum dot light-emitting layer, an electron transport layer and a cathode stacked in sequence; characterized in that: The quantum dot light-emitting layer comprises quantum dots, the quantum dots comprise a core body and a shell layer covering the core body, and the surface of the core body is etched and passivated simultaneously by an inorganic acid / acid and chloride; The electron transport layer includes an electron transport material, and the electron transport material is passivated by chloride.

2. The long-life electroluminescent device according to claim 1, characterized in that: Include one or more features selected from the following groups: (1) The anode substrate comprises: a substrate and an anode; (2) The hole injection material of the hole injection layer includes: transition metal oxide nanowires, or conductive polymer PEDOT:PSS; (3) A hole transport layer is also provided between the hole injection layer and the quantum dot light emitting layer; (4) The material of the cathode includes at least one of aluminum, magnesium, calcium, silver and their alloys.

3. The long-life electroluminescent device according to claim 1, characterized in that: The core of the quantum dot is an element of group IIB-VIA; Preferably, the core of the quantum dots includes: ZnSe, ZnTe, ZnSeTe, ZnSeS, ZnSTe, CdSe, CdTe, CdSeTe, CdSeS, CdSTe, CdZnS, CdZnSe, CdZnTe, HgS, HgSe, HgTe, HgSeS, HgSeTe, HgSTe, CdHgS, CdHgSe, CdHgTe, HgZnS, HgZnSe, HgZnTe, HgZnTeS, CdZnSeS, CdZnSeTe, CdZnSTe, CdHgSeS, CdHgSeTe, CdHgSTe, HgZnSeS, HgZnSeTe, HgZnSTe or a combination thereof.

4. The long-life electroluminescent device according to claim 1, characterized in that: The inorganic acid / acid includes at least one of hydrofluoric acid, hydrogen chloride, sulfuric acid, formic acid, acetic acid, sodium fluoride, aluminum fluoride, calcium fluoride, lead tetrafluoride, phenylcarbonyl fluoride, tetrabutylammonium fluoride, fluoroacetamide, or sodium fluoroacetate.

5. The long-life electroluminescent device according to claim 1, characterized in that: The chloride is composed of metal elements and chlorine elements; Preferably, the chloride includes at least one of zinc chloride, potassium chloride, sodium chloride, copper chloride, magnesium chloride, calcium chloride, ferric chloride, ferrous chloride, or aluminum chloride.

6. The long-life electroluminescent device according to claim 1, characterized in that: The electron transport material includes: metal oxides, core-shell structure metal oxides, element-doped metal oxides, and element-doped core-shell structure metal oxides; Preferably, the metal oxide includes: at least one of zinc oxide, magnesium oxide, zinc magnesium oxide, aluminum oxide, and zinc aluminum oxide; the core-shell structured metal oxide includes: at least one of zinc magnesium oxide / magnesium oxide, zinc magnesium oxide / zinc oxide, zinc oxide / magnesium oxide, zinc aluminum oxide / magnesium oxide, zinc aluminum oxide / zinc oxide, zinc aluminum oxide / aluminum oxide, and zinc oxide / aluminum oxide; the metal oxide doped with elements or the core-shell structured metal oxide doped with elements is a metal oxide or a core-shell structured metal oxide doped with other elements, and the doping elements include: at least one of aluminum, lithium, tin, manganese, yttrium, lanthanum, copper, nickel, zirconium, cerium, and gadolinium.

7. A method for preparing a long-life electroluminescent device, the method comprising: A hole injection layer, a hole transport layer, a quantum dot light-emitting layer, and an electron transport layer are sequentially arranged on an anode substrate, and a cathode layer or a packaged cathode plate is formed on the electron transport layer to obtain an electroluminescent device; the characteristics of the device are as follows: The quantum dot light-emitting layer includes quantum dots, after synthesizing the quantum dot core body, adding inorganic acid / acid and chloride to etch and passivate it, and then synthesizing the shell layer covering the core body; The electron transport layer includes an electron transport material. When synthesizing the electron transport material, chloride is added to passivate it to form Cl - Passivated electron transport materials.

8. The method for preparing a long-life electroluminescent device according to claim 7, characterized in that: Add the inorganic acid / acid and chloride in a molar ratio of 1:(200-5000); Preferably, the inorganic acid is added in a molar ratio of acid to chloride of 1:(500-2000).

9. The method for preparing a long-life electroluminescent device according to claim 7, characterized in that: The diameter of the core is 4.0-4.5 nm, and the thickness of the shell is 2.4-3.5 nm.

10. The method for preparing a long-life electroluminescent device according to claim 7, characterized in that: When the electron transport material is a metal oxide or a metal oxide doped with an element, the chloride is added after the metal oxide or the metal oxide doped with an element is synthesized; when the electron transport material is a core-shell structured metal oxide or a core-shell structured metal oxide doped with an element, the core-shell structured metal oxide or the core-shell structured metal oxide doped with an element comprises an oxide core and an oxide shell layer covering the oxide core, and after the oxide core is synthesized, the chloride is added, and then the oxide shell layer is synthesized.

Citation Information

Patent Citations

  • A hybrid hole injection layer QLED device and its fabrication method

    CN110729406B

  • QLED device, preparation method thereof and display panel

    CN116156915A